2022
DOI: 10.1111/sms.14257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plyometric training on different 8‐week training intensity distributions in well‐trained endurance runners

Abstract: The aim of this four‐armed parallel group randomized‐controlled trial was to evaluate if plyometric training could have different effects on running performance and physiological adaptations depending on the training intensity distribution (TID) in an 8‐week intervention in endurance athletes. Sixty well‐trained male runners (age: 34 ± 6 years, relative ⩒O2peak: 69 ± 3 ml kg−1 min−1) were recruited and allocated to a pyramidal (PYR), pyramidal + plyometric training (PYR + PLY), polarized (POL), and polarized +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The Manova test results showed significant differences between the three groups' increasing speed, agility, and leg muscle power in badminton players (p<0.05). However, the results of the post hoc test showed that there was a significant difference between the group given the combination treatment of plyometric and ladder drill exercises (Group TR and SH) and Fernandez-Fernandez et al, 2016;Filipas et al, 2023;Guo et al, 2021;Lu et al, 2022;Ozbar et al, 2014), as well as the ladder drill training program. The results of this study which stated that there were no significant differences in the TR (tuck jumpdouble leg run) and SH (squat jump-double leg hop) groups, were in line with several previous studies, even though the plyometric tuck jump and squat jump exercises were both can improve the performance of the physical condition of leg muscle power, but there is no known significant difference between the two (Ashari et al, 2019;Falah & Pranatahadi, 2019;Ratno & Darmawan, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…The Manova test results showed significant differences between the three groups' increasing speed, agility, and leg muscle power in badminton players (p<0.05). However, the results of the post hoc test showed that there was a significant difference between the group given the combination treatment of plyometric and ladder drill exercises (Group TR and SH) and Fernandez-Fernandez et al, 2016;Filipas et al, 2023;Guo et al, 2021;Lu et al, 2022;Ozbar et al, 2014), as well as the ladder drill training program. The results of this study which stated that there were no significant differences in the TR (tuck jumpdouble leg run) and SH (squat jump-double leg hop) groups, were in line with several previous studies, even though the plyometric tuck jump and squat jump exercises were both can improve the performance of the physical condition of leg muscle power, but there is no known significant difference between the two (Ashari et al, 2019;Falah & Pranatahadi, 2019;Ratno & Darmawan, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Training adaptations following the same training intervention deviate substantially in different individuals [12][13][14][15], a nding that persists in monozygotic twins possessing the same genotype [14]. On average, increases in knee extensor muscle strength and VȮ 2max were observed following 3 months of strength training and endurance training respectively, but with large inter-individual differences [14].…”
mentioning
confidence: 98%
“…Recently, it was shown that combining polarised endurance training with plyometric strength training resulted in the highest performance gains in elite runners compared to pyramidal endurance training, where 80% of the time was spent in the low-to-moderate intensity domain and the nal 20% was spent primarily at heavy intensities (i.e. between the rst and second lactate/ventilatory thresholds) [12]. Given that individual training responses differ considerably, even following the same training and in individuals with the same genotype, coaches and athletes could bene t from individual predictions of anticipated changes in performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation